2021
DOI: 10.1098/rsos.210196
|View full text |Cite
|
Sign up to set email alerts
|

Domestic egg-laying hens,Gallus gallus domesticus, do not modulate flapping flight performance in response to wing condition

Abstract: Wild birds modulate wing and whole-body kinematics to adjust their flight patterns and trajectories when wing loading increases flight power requirements. Domestic chickens ( Gallus gallus domesticus ) in backyards and farms exhibit feather loss, naturally high wing loading, and limited flight capabilities. Yet, housing chickens in aviaries requires birds to navigate three-dimensional spaces to access resources. To understand the impact of feather loss on laying hens' flight capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…It is possible that an increase in power output would result in more rapid fatigue of the flight muscles, and hens may opt to use ground resources to avoid associated energetic costs; however, this would require further investigation. In addition to an increase in wing loading, lost and damaged flight feathers are known to result in stability challenges [ 25 ], reduced aerodynamic efficiency [ 7 ] and poor maneuverability [ 19 ]. All these factors may cause a reduction in elevated resource access.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that an increase in power output would result in more rapid fatigue of the flight muscles, and hens may opt to use ground resources to avoid associated energetic costs; however, this would require further investigation. In addition to an increase in wing loading, lost and damaged flight feathers are known to result in stability challenges [ 25 ], reduced aerodynamic efficiency [ 7 ] and poor maneuverability [ 19 ]. All these factors may cause a reduction in elevated resource access.…”
Section: Discussionmentioning
confidence: 99%
“…While these consequences would make flying upwards to access resources difficult, they may also result in challenges in descending safely from platforms. Even when fully feathered, it has been shown that laying hens descend at a velocity of approximately 3.94 m s −1 [ 19 ], compared to the 0.92 m s −1 and 0.85 m s −1 of the Zebra Finch ( Taeniopygia guttata ) and Diamond Dove ( Geopelia cuneata ), respectively [ 32 ]. This means that laying hens move downwards at a fast rate, which can result in injuries or pain upon impact with the ground.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some pecking is part of their natural behavior, SFP is a major behavioral problem as it causes feather cover damage and can develop into cannibalism ( 2 ). Birds rely on intact feather cover for thermoregulation/insulation and water-proofing ( 3 ), locomotion, and navigation of the environment ( 4 , 5 ), and social communication ( 6 ). SFP is deleterious to the health and welfare of farmed birds.…”
Section: Introductionmentioning
confidence: 99%
“…Certain chicken breeds are known to have only limited flight capacity or even completely lost their flight capacity ( e.g. , ukokkei and Polish breeds) and this is largely attributed to the unfitness of their plumage for such task ( Ekarius, 2007 ; León et al, 2021 ). Differences in flight capacity have also been reported depending on the weight of the breed: the heavier, the less prone to sustained flight ( Darwin, 1868 ; Schippers, Simons & Kippen, 2013 ).…”
Section: Introductionmentioning
confidence: 99%